Evaluation of Chromosomal Aberrations and Micronuclei in Medical Workers Chronically Exposed to Low Dose Ionizing Radiation - Yanti Lusiyanti; Iin Kurnia; Viria Agesti Suvifan; Sardini Sardini; Sofiati Purnami; Nastiti Rahajeng (Biosaintifika: Journal of Biology & Biology Education, 2017)
Medical workers representing the group is the most consistently are exposed to low doses of ionizing radiation, prolonged low-level ionizing radiation can induce chromosomal aberrations (CAs). This study would evaluate the cytogenetic effect using the CAs based on dicentric, and cytokinesis-blocked micronucleus (CBMN)  assay on hospital workers. The exposed group dividedto Interventional and Diagnostic groups then compared to non exposed group. The accumulated absorbed doses calculated for the radiation workers were below 5mSv. Blood samples were obtained from 29 samples of medical workers , and 15 samples of control. The Study showed that the frequency of  dicentric chromosomes both in exposed  and control  were not found. In case of micronuclei, the mean frequencies were observed in exposed group that was (19 ±6.22) and (16.25 ± 6.04) respectively and the control group was (10.4±7.79). Frequency MN/1000 cell in the lymphocytes both in the two exposed group was relatively higher  compared to control group. However the  MN frequencies in all sample  group was still in normal range . In this study chronic low radiation dose exposure in the hospital  had no significant effect on chromosome aberration nor micronuclei. The benefit of the study  is to enrich the potential usefulness of cytogenetic assay providing safety  index in medical surveillance programs. The results suggest that education and retraining of staff concerning radiation safety guidelines  need to be done to maintain the safety aspects of radiation.